2016
DOI: 10.1001/jamacardio.2015.0386
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Subsequent Shocks After Initial Implantable Cardioverter-Defibrillator Discharge and Implications for Driving Restrictions

Abstract: In this large cohort of ICD recipients, the incidence of a second shock after an initial ICD discharge was lower than previously reported and depended on several programmed ICD variables. These data, with future research to derive contemporary estimates of the likelihood of fatality resulting from an ICD shock while driving, should support the development of evidence-based guidelines for driving restrictions in ICD recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
18
1
1
Order By: Relevance
“…It could also be argued that using overall shock incidence from trials could overestimate incapacitation risk as a portion of the shocks are inappropriate and thus are associated with a lower incidence of syncope. The cut‐off of acceptable risk of harm of 5 in 100 000 (0.005%) was described in a Canadian road safety study published in 1987 and has been used and accepted widely since, with previous concerns raised as to its validity in the current era with newer vehicle types and driving practices . Furthermore, a model that creates a binary classification of safety based on a point result within a continuous estimate of risk, as seen here, can induce a false sense of confidence in the clinician; a small variance in the parameters can result in a patient being deemed safe or unsafe.…”
Section: Introductioncontrasting
confidence: 84%
See 2 more Smart Citations
“…It could also be argued that using overall shock incidence from trials could overestimate incapacitation risk as a portion of the shocks are inappropriate and thus are associated with a lower incidence of syncope. The cut‐off of acceptable risk of harm of 5 in 100 000 (0.005%) was described in a Canadian road safety study published in 1987 and has been used and accepted widely since, with previous concerns raised as to its validity in the current era with newer vehicle types and driving practices . Furthermore, a model that creates a binary classification of safety based on a point result within a continuous estimate of risk, as seen here, can induce a false sense of confidence in the clinician; a small variance in the parameters can result in a patient being deemed safe or unsafe.…”
Section: Introductioncontrasting
confidence: 84%
“…Merchant et al 12 performed a retrospective analysis of over 14 000 patients who had received an ICD shock. They confirmed the proposition that a shock from their ICD places a patient at a higher risk of receiving a further shock, with over 50% of patients receiving a second shock within 3 years.…”
Section: Incidence Of Shock In Patients With Icdmentioning
confidence: 54%
See 1 more Smart Citation
“…U takvim slučajevima moderna se terapija zasniva na ugradnji kardioverterskog defibrilatora (ICD). Osobe s ovim tipom ELS-a usprkos ciljanoj primjeni elektrošoka izložene su riziku od simptomatske ventrikulske aritmije sa sinkopom ili pomućenjem svijesti i time su pri vožnji rizik ne samo za sebe već i za druge 22 . Recentna ispitivanja provedena u Kanadi pokazala su da se na 100 000 pacijenta s ICD-om samo u njih 5 godišnje pojavi simptomatska aritmije.…”
Section: Arrhythmiasunclassified
“…In such cases, current therapy is based on implantable cardioverter defibrillator (ICD). Individuals with this type of pacemaker are at a risk of symptomatic ventricular arrhythmia with syncope or impaired consciousness in spite of targeted electrical stimulation, thus posing a risk while driving not only for themselves but also for other traffic participants 22 . Recent studies conducted in Canada showed that symptomatic arrhythmia occurred in only 5 per 100,000 patients with ICD per year.…”
Section: Rasprava I Zaključakmentioning
confidence: 99%